(untitled) (Literary Voice, 2024)
The paper aims at exploring Victorian poet Christina Rossetti’s poem (1830-1894) “Goblin Market” (1862) through psychoanalytical and feminist perspectives. The poem which is an ostensible tale meant to be narrated to children, is actually on a deeper level, a thematically voluminous piece of literature from which a plethora of meanings emerge. What this poem demonstrates, holds true in the contemporary times. The objectives of this paper are to analyze 1) the poem with reference to studying gender as a construct, established by the patriarchal discourses, and also 2) the complexes that an individual might undergo owing to repression. The paper makes use of Luce Irigaray (b. 1930) and Helene Cixous’ (b. 1937) notions of feminism and Freud (1856-1939) and Lacan’s (1901-1981) theories of psychoanalysis. After explaining the relevant theory, the researchers aim to apply it to “Goblin Market” in order to compare and contrast the poem from the two said perspectives. Feminism helps in deconstructing the patriarchal overtones and power relationships whereas psychoanalysis enables the readers to understand the complexes and experiences that individuals undergo owing to their psychological make-up.